2007
DOI: 10.1002/mrd.20795
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol increases muscle fiber size and GATA‐2 protein in rat skeletal muscle in utero

Abstract: Certain beta(2)-adrenoceptor agonists, such as clenbuterol, are known to elicit a muscle-specific anabolism or hypertrophy in both normal and catabolic muscle in a wide variety of species. However, the underlying mechanism(s) of the beta(2)-agonist-induced anabolism remains unclear. This study aimed to determine the effects of clenbuterol administration in utero on skeletal muscle and to examine the underlying molecular mechanisms. Pregnant rats were fed clenbuterol (2 mg/kg diet) from Day 4 of gestation (4 dg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…63 gestation, term w150 days) did not increase weight or alter body composition of neonatal twin lambs, with the exception of increased heart weight (Shackelford et al 1995). Similarly in rats, fetal weight in late pregnancy and weight of neonatal pups were not changed by feeding pregnant dams the b 2 -adrenergic agonist clenbuterol from day 4 after mating and throughout pregnancy, although neonatal cardiac hypertrophy was also reported in this species (Maltin et al 1990, Downie et al 2008. Limited studies in women with suspected impaired fetal growth have also found no change in birth weight in response to short-term treatment with the b-adrenergic agonist ritodine in late pregnancy (Say et al 2001).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…63 gestation, term w150 days) did not increase weight or alter body composition of neonatal twin lambs, with the exception of increased heart weight (Shackelford et al 1995). Similarly in rats, fetal weight in late pregnancy and weight of neonatal pups were not changed by feeding pregnant dams the b 2 -adrenergic agonist clenbuterol from day 4 after mating and throughout pregnancy, although neonatal cardiac hypertrophy was also reported in this species (Maltin et al 1990, Downie et al 2008. Limited studies in women with suspected impaired fetal growth have also found no change in birth weight in response to short-term treatment with the b-adrenergic agonist ritodine in late pregnancy (Say et al 2001).…”
Section: Discussionmentioning
confidence: 84%
“…In lambs, in utero exposure to the b 2 -adrenergic agonist L 644,969 from day 25 to 95 of pregnancy also did not alter fiber type proportion or size in young adult offspring (Shackelford et al 1995). In contrast, feeding rats the b 2 -adrenergic agonist clenbuterol throughout most of pregnancy and through lactation increased muscle fiber size but decreased muscle weights and secondary:primary fiber ratios in fetuses (Maltin et al 1990, Downie et al 2008. This decreased muscle weight persisted postnatally, with a decrease in total fiber numbers (Maltin et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Clenbuterol caused an impairment of collagen turnover by down-regulating MMP-9 activity [11]. Clenbuterol not only enhanced muscle fiber size but also increased expression of GATA-2 protein in skeletal muscle of rat uterus [12]. The preferential involvement of calpain 2 autolysis was found for clenbuterol-induced skeletal muscle remodelling in rats [13].…”
Section: Introductionmentioning
confidence: 96%
“…We have previously identified the β‐adrenergic signalling pathway as a potential novel regulator of skeletal muscle regeneration 4,5 . In addition, we and others have postulated a role for β‐adrenoceptors in skeletal muscle growth 6 and development 7 …”
Section: Introductionmentioning
confidence: 97%